Hotspotting: Development of an Interprofessional Education and Service Learning Program for Care Management in Home Care Patients. Issue 5 (September 2018) - Zomorodi, Meg; Odom, Trish; Askew, Naomi C.; Leonard, Christina R.; Sanders, Kimberly A.; Thompson, Daniel
Abstract : The purpose of this article is to describe a service learning opportunity where interprofessional teams of students worked together to address patients' social determinants of health through home visits. This article describes this process, known as "hotspotting, " and presents the development of this project, including collaboration with a local home health agency, recruiting of students, and weekly team meetings for debriefing. Evaluation data, barriers with implementation, and next steps for sustainability are also discussed.